‘Going off the Beaten Path’: Knut Hamsun’s Forays into Travel Writing - Conner, Tom (Nordlit, 2016)
This paper examines Knut Hamsun’s travel writing, from his many newspaper articles about America published before The Cultural Life of Modern America (Fra det moderne Amerikas aandsliv, 1889) – his idiosyncratic and very personal reckoning with America – to his only real (i.e., formal) travelogue or travel book, In Wonderland (I Æventyrland, 1903), documenting his visit to the Russian Caucasus. The article focuses on some common themes as well as striking differences among these works, so as to highlight Hamsun’s creative use of the travel genre. As the term “foray” in my title suggests, there is something illicit and transgressive about Hamsun’s travel writing. He does not readily conform to the norms of the genre; rather, he transforms the genre to suit his own purposes by infusing a large dose of his idiosyncratic genius in everything he writes about the faraway lands he visits.
Keywords: America; autobiography; capitalism; Caucasus; globalization; Hamsun; materialism; memoirs; Russia; transgression; travelogue; travel writing